Pengaruh Brand Image, Promosi dan Online Customer Rating Terhadap Keputusan Pembelian Skincare Avoskin Pada Shopee - Faiz Sidqi Robbani; Riyandi Nur Sumawidjaja; Dadan Abdul Aziz Mubarok (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The decision to purchase skincare through a marketplace is formed in situations where consumers have extensive access to information but cannot inspect the product in person. This study examines the role of brand image, promotion, and online customer ratings in explaining the purchase of Avoskin products through Shopee. Data were obtained from 100 consumers residing in Bandung City, who had purchased Avoskin through Shopee, and were selected based on research criteria. Respondents' responses were collected using a five-level questionnaire and analyzed through multiple linear regression after examining the instrument's quality and model requirements. The findings indicate that brand perception and online customer ratings are positively related to purchase decisions. In contrast, promotion did not demonstrate a convincing partial contribution when the other two variables were analyzed in the same model. Among the tested predictors, online customer ratings produced the largest standardized coefficient. The three variables collectively explained 38.9% of the variation in purchase decisions. These results indicate that in online skincare transactions, consumers rely more on brand reputation and previous user experience than on promotions readily available in various stores. For Avoskin, strengthening consumer decisions needs to be done through quality consistency, post-purchase experience management, handling negative evaluations, and promotional programs tailored to skin needs and product understanding.